2008
DOI: 10.1002/adma.200703096
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the External Quantum Efficiency of a Silicon Quantum Dot Light‐Emitting Diode by Localized Surface Plasmons

Abstract: Effective light emission from low-dimensional silicon materials such as porous silicon, silicon nanocrystals, and superlattices has been demonstrated at room temperature in spite of the indirect bandgap nature of bulk silicon. [1][2][3][4][5] In particular, silicon quantum dot (Si QD) light-emitting diodes (LEDs) have recently been investigated as a promising light source for the next generation of optical interconnections. [6][7][8] However, the quest for highly efficient Si QD LEDs remains unfulfilled. To ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 32 publications
(28 reference statements)
2
76
0
Order By: Relevance
“…For example, Yeh et al [13] have recently enhanced the InGaN/GaN LED emission intensity by 150% relative to a LED without an Ag layer. Kim et al [3] reported a 4.3-fold EL enhancement of Si-QDs LED by QD-Ag coupling. In Cheng et al's [16] report on the ZnO films, a maximum photoluminescence (PL) enhancement factor of 3 was achieved via SPs.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Yeh et al [13] have recently enhanced the InGaN/GaN LED emission intensity by 150% relative to a LED without an Ag layer. Kim et al [3] reported a 4.3-fold EL enhancement of Si-QDs LED by QD-Ag coupling. In Cheng et al's [16] report on the ZnO films, a maximum photoluminescence (PL) enhancement factor of 3 was achieved via SPs.…”
Section: Introductionmentioning
confidence: 98%
“…SPs are the collective oscillations of free electrons in a metal, which occur at the interfaces between metals and dielectrics [2]. In addition to the propagating surface plasmons (PSPs) on a plane surface, the collective oscillations of electrons in metal nanoparticles embedded in a dielectric matrix are localized surface plasmons (LSPs) [3,4]. Either PSP or LSP can interact with nearby light emitter through its evanescent or near-field coverage for enhancing emission [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPs are the collective oscillations of free electrons in a metal, which occur at the interfaces between metals and dielectrics [4]. In addition to the propagating surface plasmons (PSPs) on a plane surface, the collective oscillations of electrons in metal nanoparticles embedded in a dielectric matrix are localized surface plasmons (LSPs) [5,6]. Either PSP or LSP, an SP can interact with the light emitter nearby through its evanescent or near-field coverage for enhancing emission [7].…”
Section: Introductionmentioning
confidence: 99%
“…The emission efficiency is enhanced via an alternative radiation channel, in which the energy of the light emitter is firstly transferred into the propagating or localized SP modes and then into the radiation modes [8]. In the past two decades, SPs have been extensively studied to enhance the luminescence efficiency of light emitting materials and devices, such as InGaN/GaN [3,6,9,10], silicon quantum dots (Si-QD) [5] and ZnO films [11][12][13][14][15][16], for the applications of ultrabright light-emitting diodes (LEDs), or ultraviolet UV lasers. In our previous studies, SPs were successfully used to enhance the light emission from a-Si 1 − x C x :H films (emitting blue-green light at 480 nm) [17] and a-C:H films (emitting blue light at 445 nm) [18].…”
Section: Introductionmentioning
confidence: 99%